Trade and Commercial Relations Between Poland and the Military Governments of the US/UK and French Zones of Occupation in Germany 1946–1949 – Trade Agreement, List of Products, Payments Agreement: Introduction and development Tadeusz Janicki - Janicki, Tadeusz (Studia Historiae Oeconomicae, 2018)
Trade and Commercial Relations Between Poland and the Military Governments of the US/UK and French Zones of Occupation in Germany 1946–1949 – Trade Agreement, List of Products, Payments Agreement